Low doses in hormone therapy of the menopausal period - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2006)
Low doses of oestrogens and progestogens are becoming increasingly popular types of hormone therapy (HT) in women during the menopausal period. Low-dose HT, with its similar therapeutic efficacy, gives fewer side-effects to a patient than standard doses of hormones do. It is recommended to prefer this type of HT when commencing hormonal therapy as well as in all females with increased risk of cardiovascular and oncological diseases.